Pemberdayaan Masyarakat dalam Pemahaman dan Optimalisasi Lingkungan Sehat di Desa Salak Kecamatan Randuagung Kabupaten Lumajang Jawa Timur - Maghfiroh, Eva; Hidayatullah , Indra; Parino, Parino; Moh Yusuf, Thorieq (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
This community service aims to examine community empowerment in understanding and optimizing a healthy environment in Salak Village, Randuagung District, Lumajang Regency, East Java. This study uses a participatory action research method with FGD techniques for collecting data through interviews and observations. The results of the study indicate that the people of Salak Village do not yet have sufficient understanding of the importance of a healthy environment and do not yet have the ability to optimize their surrounding environment. However, with community empowerment through training and mentoring, the community can have sufficient knowledge, skills, and awareness to optimize a healthy environment and improve their quality of life. This study recommends that community empowerment must be carried out sustainably and involve all relevant stakeholders.